Source-dependent optical properties and molecular characteristics of atmospheric brown carbon - J. Zhai; J. Zhai; Y. Zhang; Y. Zhang; P. Liu; Y. Zhang; Y. Zhang; A. Zhang; A. Zhang; Y. Zeng; Y. Zeng; B. Cai; et al. (Atmospheric Chemistry and Physics, 2025)
Atmospheric brown carbon (BrC) can significantly affect Earth's radiation budget by its wavelength-dependent absorption in the ultraviolet–visible (UV–vis) range. BrC consists of a wide variety of organics with different optical properties, making accurate climate modeling essential for understanding its radiative impact. Here, we conducted a field campaign during the summer in Shenzhen, China, to investigate the optical properties and molecular characteristics of BrC from diverse particle sources using both online and offline measurements. BrC mass concentrations were determined based on either thermally desorbed organic carbon or water-soluble organic carbon (WSOC), and the corresponding mass absorption cross-sections (MACs) were calculated accordingly. Different sources of BrC, including those from secondary production associated with ozone pollution, urban transportation, and biomass burning, were identified through meteorological data and particle chemical compositions. The results show that the MAC of BrC varied across sources, with BrC from biomass combustion exhibiting the highest MAC at 370 nm (3.42 ± 0.41 m2 g−1) and secondary BrC associated with ozone pollution showing the lowest (1.25 ± 0.56 m2 g−1). Nevertheless, secondary BrC exhibited the highest absorption Ångström exponent (AAE), while the BrC from biomass burning had the lowest AAE. Molecular analysis revealed that species in the CHON family from biomass burning demonstrated the strongest light absorption. Our results provide valuable insights for quantifying the source-specific optical properties of BrC, enhancing the accuracy of climate models.